Link Between T2DM And Alzheimer's disease - Ashraf, Kariman Ashraf (faculty of Basic Medical Science - Libyan International Medical University, 2018)
The aim of this paper is to provide a comprehensive review of the epidemiological evidence linking that suggest a possible shared pathophysiology between type 2 diabetes mellitus (T2DM) and Alzheimer's disease (AD). It has even been hypothesized that AD might be ‘type 3 diabetes’. The present review summarizes some of the evidence for the possible link including insulin processing, acetylcholine, Inflammation ,Obesity and metabolic syndrome ,Mitochondria and oxidative stress. The evidence for a connection between T2DM and AD is based upon a variety of diverse studies, but definitive biochemical mechanisms remain unknown. Additional study is needed to prove the existence or the extent of a link between T2DM and AD, but sufficient evidence exists to warrant further study
Type 2 diabetes mellitus (T2DM) and Alzheimer's disease (AD) are both more prevalent with ageing, but it has generally been assumed that this is coincidental, not a reflection of co-morbidity. However, evidence suggests that patients with T2DM are at an increased risk of getting AD and that hyperinsulinaemia and insulin resistance hallmarks of T2DM can lead to memory impairment The latest research is focused on Alzheimer’s disease, the most common neurodegenerative disorder that accounts for 60–80% of cases of dementia and one for which it’s harder to figure out the precise relationship with diabetes. On this much, many scientists agree: The rate of Alzheimer’s disease could be cut by close to half if diabetes could be abolished. The connection between the two is so strong that Suzanne M. de la Monte, one of the top researchers in the field, has said that many cases of Alzheimer’s could be dubbed Type 3 diabetes. People who haven’t necessarily developed diabetes might still develop insulin resistance in the brain, said de la Monte, a professor of neurosurgery, pathology and laboratory medicine at Brown University.That’s why she uses the term Type 3 diabetes